Persepsi Mahasiswa PGSD terhadap Cakupan Industri dalam Program Magang Berdampak - A. Muh. Ali (GENIUS: Jurnal Inovasi Pendidikan dan Pembelajaran, 2025)
The purpose of this study was to describe the perceptions of students in the Elementary School Teacher Education (PGSD) Study Program at Makassar State University regarding the relevance, challenges, and expectations of the Impact Internship Program. This program is part of the Independent Learning and Independent Campus policy, which aims to provide students with real-world work experience. However, for PGSD students, this policy faces obstacles because elementary schools are not yet recognized as part of the industry. This study used a quantitative descriptive method by distributing questionnaires to students. The results showed that most students understood the importance of the program but experienced confusion because the available internship locations did not align with the educational field. They also hoped that schools and non-formal educational institutions would be recognized as part of the "education industry." These findings emphasize the need to review and redefine the concept of industry in the MBKM policy to make the implementation of the Impact Internship Program more relevant for prospective elementary school teachers.